Effects of nurse shrubs and tree shelters on the survival and growth of two Austrocedrus chilensis seedling types in a forest restoration trial in semiarid Patagonia, Argentina - Urretavizcaya, María Florencia (2012)
Context. Harsh environmental conditions in xeric sites of Andean Patagonia, affect the emergence, survival, and growth of either naturally grown or planted Austrocedrus seedlings. Aims. We evaluated the effects of nurse shrubs and tree shelters on the survival and growth of Austrocedrus seedlings as compared to unprotected (control) areas and how differently produced seedling types perform under these treatments. Methods. In 2006, two Austrocedrus seedling types (1+2 S1 and Plug 2+1 S2) were planted under shrub cover (C1),tree shelter (C2), and control (C3). Soil surface temperature and moisture were measured for each treatment during the first growing season, while seedling survival and height were recorded during 5 years. Results. Survival was not affected by cover type the first year, but it was affected by seedling type (S1>S2). After an extremely dry second growing season, seedling survival significantly decreased in relation to either cover or seedling type. Five years after plantation, survival was significantly higher for C1 and C2 (40?60 %) as compared to C3-S2 (18 %). Seedling height was significantly affected by cover, but not by seedling type. Conclusions. The use of nurse shrubs and/or tree shelters is useful in Austrocedrus seedling restoration trials. Seedling morphology appears as relevant for survival in semiarid environments.